1991
DOI: 10.1136/jnnp.54.2.145
|View full text |Cite
|
Sign up to set email alerts
|

The interpretation of dysprosody in patients with Parkinson's disease.

Abstract: Prosodic features in the speech production of 21 patients with idiopathic Parkinson's disease were tested. The appreciation of vocal and facial expression was also examined in the same patients. Significant intergroup differences were found in the prosody production tasks but, in contrast to previous results, not in the receptive tasks on the recognition and appreciation of prosody and of facial expression. The discrepancy between the production and recognition of prosodic features does not support the suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 12 publications
0
36
1
1
Order By: Relevance
“…Indeed, about 30% of the reviewed studies did not examine its effect on the recognition of specific emotions but calculated an overall score encompassing all the displayed emotions 4, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Moreover, authors did not manipulate the same set of stimuli, and some only used a small subset 23, 30, 31, 32, 33, 34, 35.…”
Section: Facial Emotion Recognition In Pdmentioning
confidence: 99%
“…Indeed, about 30% of the reviewed studies did not examine its effect on the recognition of specific emotions but calculated an overall score encompassing all the displayed emotions 4, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Moreover, authors did not manipulate the same set of stimuli, and some only used a small subset 23, 30, 31, 32, 33, 34, 35.…”
Section: Facial Emotion Recognition In Pdmentioning
confidence: 99%
“…A commonly drawn inference is that the emotion recognition deficit experienced by individuals with PD is likely to be cross-modal (Peron et al, 2010), yet only a small number of studies have examined emotion recognition performance in both facial and prosodic modalities with same Emotional state classification in PD 4 participants. A number of these report found deficits in both modalities (Ariatti et al, 2008;Yip et al, 2003), whereas others found problems in only one modality (facial, Pell and Leonard, 2003); prosody, Pell and Leonard, 2005), and at least one failed to find deficits in recognition in either modality (Caekebeke et al, 1991).…”
Section: Introductionmentioning
confidence: 96%
“…Speech disorder can be frequent as 89% in PD and often impacts on quality of life (Aronson 1990). Impairment of emotional prosody has been suggested to be present in PD patients (Borod et al 1990;Caekebeke et al 1991;Pell 1996).…”
Section: Introductionmentioning
confidence: 99%